Analyzing the Population Retaining Ability and the Ability to Economically Provide for a Population in the Micro Region of Püspökladány - Tikász, Ildikó Edit (Acta Agraria Debreceniensis, 2007)
According to the data of population density, 98% of Hungary’s territory has rural features. Gaining EU supports, in order to focus on developing the most underdeveloped communities, and in order to decrease – not to increase – the differences between communities, the establishment of priorities and determination of the rank of rural communities based on their development potential is necessary. The claim of measurability arises because of comparison and classification. A possibility or a target area of measuring is analysing population retaining and income producing capability of rural areas. To gain adequate, many-sided information about the development potentials of a given community, micro- or macro region, complex condition survey, as well as secondary information completed with empirical data and subjective value judgment is essential. The aim in every case is to gain experience of the present condition via determining the direction of change. In this study, I deal with the clarification of the definition of population retaining ability and the ability to economically provide for a population and introduce the most important results of the inquiry with questionnaires completed in the frame of an empirical survey.